Hybrid war and its repercussions on the security and economy of syria - زينه, باسل (Latakia University Journal - Economic and Legal Sciences Series, 2024)
The global war broke out on Syria in March 2011, after Syria was moving clearly towards a social market economy - despite some reservations about some neoliberal economic policies - and achieved good results in terms of the growth rate of the gross domestic product, encouraging foreign investments, and establishing industrial cities.. ...... However, this process stopped after the hybrid war on Syria in 2011, and the catastrophic effects and crises it left on the various sectors of the state, on the components of the gross domestic product, and on inflation levels, thus greatly affecting purchasing power. Which made us take a look at the economic conditions before the war and during the war, so that we may benefit from the mistakes of the past in the stage of reconstruction and development.